Overview of cerebral cavernous malformations: comparison of treatment approaches - Bubenikova, Adela; Skalicky, Petr; Benes, Vladimir; Benes, Vladimir; Bradac, Ondrej (Journal of neurology, neurosurgery, and psychiatry, 2022)
OBJECTIVES: The comparison of treatment efficacy for cerebral cavernous malformations (CCMs) has not yet been well researched. DESIGN: PubMed, Cochrane Library, Science Direct, ISI Web of Science, Embase and additional sources were searched to identify cohort studies about the treatment of CCMs published between 1990 and 2020. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed; the Newcastle-Ottawa Scale was used to assess the risk of bias and to evaluate limitations based on selection/outcome biases. The cumulative incidences with 95% CIs were calculated using the random effects model. The models of Poisson distribution were applied to evaluate risk factors of poorer treatment outcome by calculating rate ratios within 100 person-years with 95% CIs. RESULTS: A total of 100 cohorts yielding 8994 patients treated for CCMs within 41 098 person-years of follow-up were analysed. The efficacy of ensuring the prevention of haemorrhage was 97% in surgical, 86% in radiosurgical and 77% in the conservative treatment. The lowest mortality (1%) was after radiosurgery, and the highest persistent morbidity (22%) was in natural history series. Deep-seated and brainstem CCMs were associated with higher bleeding rates. Lobar localisation was a protective factor in all analyses. Patients with history of previous haemorrhage were exposed to higher risk of rebleeding. Male gender was a protective factor associated with lower risk of post-treatment haemorrhage. CONCLUSIONS: Surgical resection of CCM is effective in ensuring the prevention of haemorrhage with acceptable morbidity and mortality, but conservative and radiosurgical management is a justified treatment alternative. Brainstem and deep-seated CCMs are predominantly associated with higher haemorrhage rates.
Keywords: výsledek terapie; Brain Stem; radiochirurgie; mužské pohlaví; surgery; Humans; systematic reviews; mozkový kmen; Hemangioma, Cavernous, Central Nervous System; Radiosurgery; Treatment Outcome; kavernózní hemangiom centrálního nervového systému; lidé; Male; meta-analysis